Reconceptualising the scholarship of marketing education–SoME futurescapes. Issue 2 (May 2018) - Snuggs, Elizabeth; Jevons, Colin
Highlights: A call to action for improving the standing of research in marketing education. Coins the term "SoME, Scholarship of Marketing Education". Provides three futurescapes for scholars to consider. Abstract: Teaching is an important part of marketing academics' work. However research into the scholarship of marketing education (SoME) has not enjoyed the same standing as discipline-based research, a regrettable gap. We present comparative data from other business disciplines, which all value educational research higher than the marketing discipline does. We then discuss the underlying factors and collate various scenarios into three futurescapes as bases for discussion of how to increase SoME's value and reputation in a rapidly-changing environment. Chinese Abstract: 教学是市场营销学术人士工作的重要部分. 可是, 对市场营销教育的学术知识 (SoME) 的研究并未拥有与学科型研究相同的地位, 这一差距令人遗憾. 我们展示了来自其他商业学科的比价数据, 这些学科均比市场营销科学更加看重教育研究. 然后, 我们讨论了潜在因素, 并将各种不同的情境整理成三项"未来展望", 作为"在快速变化的环境中如何提高 SoME 的价值和声誉"的讨论依据.